Foreign trade in gas and electricity in North America : a legal and historical study - Miller, John Thomas (New York : Praeger Publishers, 1970)
This is a legal and historical study, foreign trade in gas and electricity in North America. It provides a comprehensive history of the development of international trade in gas and electricity between the United States and its Canada and Mexican neighbors, and the governmental regulatory responses.
Includes bibliographical references.
II 16/01/2019
Loans
Keywords: Electric utilities; Natural gas